Selective Detection of Erythrocytes with QCMs—ABO Blood Group Typing - Usman Latif; Alexandra Seifner; Franz L. Dickert (Sensors, 2023)
Blood transfusion, as well as organ transplantation, is only possible after prior blood group (BG) typing and crossmatching. The most important blood group system is that of Landsteiner’s ABO classification based on antigen presence on the erythrocyte surfaces. A mass sensitive QCM (quartz crystal microbalance) sensor for BG typing has been developed by utilizing molecular imprinting technology. Polyvinylpyrrolidone (crosslinked with N,N-methylenebisacrylamide) is a favorable coating that was imprinted with erythrocytes of different blood groups. In total, 10 MHz quartz sheets with two resonators, one for MIP (molecularly imprinted polymer) and the other for NIP (non-imprinted polymer) were fabricated and later used for mass-sensitive measurements. The structure of erythrocyte imprints resembles a donut, as identified by AFM (atomic force microscope). All the erythrocytes of the ABO system were chosen as templates and the responses to these selective coatings were evaluated against all blood groups. Each blood group can be characterized by the pattern of responses in an unambiguous way. The results for blood group O are remarkable given that all types of erythrocytes give nearly the same result. This can be easily understood as blood group O does not possess neither antigen A nor antigen B. The responses can be roughly related to the number of respective antigens on the erythrocyte surface. The imprints generate hollows, which are used for reversible recognition of the erythrocytes. This procedure is based on molecular recognition (based on supramolecular strategies), which results from size, shape and enthalpic interactions between host and guest molecules.